Moderating effect of remuneration on the relationship between flexible working hours and organization performance in public sector higher education in Pakistan: A conceptual model - Sidra, Sidra; Abdullah, Shahmir Sivaraj; Mohamad Jani, Mohamad Yusop (2017)
Higher education is critical for the social and economic development of any country. In developed countries, the performance of higher education institutions is at its peak. However, higher education in Pakistan is facing some crucial challenges.These challenges include political, social, economic and moral challenges. The Pakistani higher education sector is facing problems with low enrolment rates, disparities in gender and regions, lack of teaching material, lack of faculty members and poor infrastructure. Furthermore, Pakistani institutions are suffering from a crucial lack of resources.To address this issue and to gain a better understanding of what may improve the situation in Pakistan this conceptual paper is presented.